Pupal cases of three Nearctic species of Machimus (Diptera: Asilidae) - Dennis, D. Steve; Barnes, Jeffrey K. (Zootaxa, 2013)
The pupal cases of the Nearctic robber flies, Machimus latapex Martin, 1975, M. occidentalis (Hine, 1909), and M. prai-riensis (Tucker, 1907) are described. They are compared with the previously described pupal cases of six other Nearctic species of Machimus. The pupal case of M. latapex and facial sheaths and posterior antennal processes of M. occidentalis are illustrated.